2012
DOI: 10.1021/ja3069962
|View full text |Cite
|
Sign up to set email alerts
|

Endolysins of Bacillus anthracis Bacteriophages Recognize Unique Carbohydrate Epitopes of Vegetative Cell Wall Polysaccharides with High Affinity and Selectivity

Abstract: Bacteriophages express endolysins which are the enzymes that hydrolyze peptidoglycan resulting in cell lysis and release of bacteriophages. Endolysins have acquired stringent substrate specificities, which have been attributed to cell wall binding domains (CBD). Although it has been realized that CBDs of bacteriophages that infect Gram-positive bacteria target cell wall carbohydrate structures, molecular mechanisms that confer selectivity are not understood. A range of oligosaccharides, derived from the second… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
32
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 46 publications
0
32
0
Order By: Relevance
“…The SCWP promotes envelope attachment of murein hydrolases that specifically bind to the carbohydrate structure (18)(19)(20)(21). The ketal-pyruvyl-modified SCWP is a ligand for the S-layer homology (SLH) domains of native B. anthracis proteins.…”
mentioning
confidence: 99%
“…The SCWP promotes envelope attachment of murein hydrolases that specifically bind to the carbohydrate structure (18)(19)(20)(21). The ketal-pyruvyl-modified SCWP is a ligand for the S-layer homology (SLH) domains of native B. anthracis proteins.…”
mentioning
confidence: 99%
“…Previous work demonstrated that bacteriophage lysins of B. anthracis, PlyG and PlyL, associate with the SCWP through their C-terminal cell wall binding domain (CBD) in a manner independent of csaB-mediated ketal-pyruvylation (38,(42)(43)(44). We generated purified PlyG CBD -mCherry, where the C-terminal CBD of PlyG (38) is fused to the mCherry reporter, to assess the overall abundance and subcellular distribution of the SCWP (with or without ketal-pyruvate) in wild-type and tagO::aad9(pts-tagO i ) vegetative forms.…”
Section: B Anthracis Tago::aad9(pts-tagomentioning
confidence: 99%
“…ManNAc is a key residue of the repeating trisaccharide of the well-characterized SCWP, the only polymer known to contain ManNAc in B. anthracis (1). A library of oligosaccharides containing the core trisaccharide motif ␣-DGlcNAc-(1¡ 4)-␤-D-ManNAc-(1¡4)-␤-D-GlcNAc of the SCWP of B. anthracis was chemically synthesized with various patterns of ␣-DGal and ␤-D-Gal branching points (9). Measurement of dissociation constants for the cell wall binding domains of the endolysins PlyL and PlyG using surface plasmon resonance established a preferred interaction with a trisaccharide bearing the galactosyl moiety at C-4 of the nonreducing GlcNAc moiety (9).…”
Section: B Acillus Anthracis Elaborates the Secondary Cell Wall Polysmentioning
confidence: 99%
“…A library of oligosaccharides containing the core trisaccharide motif ␣-DGlcNAc-(1¡ 4)-␤-D-ManNAc-(1¡4)-␤-D-GlcNAc of the SCWP of B. anthracis was chemically synthesized with various patterns of ␣-DGal and ␤-D-Gal branching points (9). Measurement of dissociation constants for the cell wall binding domains of the endolysins PlyL and PlyG using surface plasmon resonance established a preferred interaction with a trisaccharide bearing the galactosyl moiety at C-4 of the nonreducing GlcNAc moiety (9). PlyL and PlyG were also found to interact with highly purified SCWP of several B. anthracis isolates via their C-terminal domains but not their Nterminal catalytic domains, thus corroborating the notion that the SCWP serves as a receptor for ␥ phage lysins (10).…”
Section: B Acillus Anthracis Elaborates the Secondary Cell Wall Polysmentioning
confidence: 99%
See 1 more Smart Citation